2023
DOI: 10.1126/science.ade9463
|View full text |Cite
|
Sign up to set email alerts
|

Lead-chelating hole-transport layers for efficient and stable perovskite minimodules

Chengbin Fei,
Nengxu Li,
Mengru Wang
et al.

Abstract: The defective bottom interfaces of perovskites and hole-transport layers (HTLs) limit the performance of p-i-n structure perovskite solar cells. We report that the addition of lead chelation molecules into HTLs can strongly interact with lead(II) ion (Pb 2+ ), resulting in a reduced amorphous region in perovskites near HTLs and a passivated perovskite bottom surface. The minimodule with an aperture area of 26.9 square centimeters has a power conversion efficiency (PCE) of 21.8% (stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(55 citation statements)
references
References 51 publications
3
52
0
Order By: Relevance
“…The CN stretch peak in BCP at 1630 cm –1 can be well distinguished. After mixing with Al powder, the CN stretching peak shifts to a smaller wavenumber of ∼1619 cm –1 , which illustrates the strong chelating interaction of BCP with Al . X-ray photoelectron spectroscopy (XPS) measurements were also performed to verify the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The CN stretch peak in BCP at 1630 cm –1 can be well distinguished. After mixing with Al powder, the CN stretching peak shifts to a smaller wavenumber of ∼1619 cm –1 , which illustrates the strong chelating interaction of BCP with Al . X-ray photoelectron spectroscopy (XPS) measurements were also performed to verify the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that there is an interaction between ibuprofen and PbBr 2 . 48 The trap density of states (tDOS) as a function of energy space 20 was calculated to look into the passivation effect of ibuprofen. As shown in Figure 2c, it is intuitively apparent that the defect state is diminished in a region of constrained energy space after ibuprofen decoration.…”
Section: Defect Passivationmentioning
confidence: 99%
“…Quasi-2D organic–inorganic halide perovskites have garnered a lot of attention in recent years due to their exceptionally high photoluminescence quantum yields (PLQYs), high carrier mobility, high color purity (half-peak width of 20 nm), adjustable band gap (light covers the entire visible), long carrier diffusion length, solution treatability, and low-cost characteristics. They have tremendous potential for applications in light-emitting diodes (LEDs), solar cells, and photodetectors . Especially, they are recognized as the star material for the next generation of light-emitting diodes, since the external quantum efficiency (EQE) of the perovskite LEDs has surpassed 20%, which includes green, red, and near-infrared light .…”
Section: Introductionmentioning
confidence: 99%
“…1–4 With power conversion efficiencies (PCEs) reaching over 25%, 5–8 state-of-the-art p–i–n devices have witnessed a gradual narrowing of the performance gap with their conventional (n–i–p) architecture counterparts of 25.7%. 6,9–11 However, the primary challenge to further enhance the performance of p–i–n PSCs is mainly correlated to hole transport materials (HTMs). 2,12–14 Notably, HTMs and semiconducting selective contacts can potentially impact the fill factor (FF), particularly for p–i–n devices, as they serve as film growth substrates at the bottom interface, which is crucial for perovskite crystallization, 13 interface defects, 15 and carrier extraction dynamics.…”
Section: Introductionmentioning
confidence: 99%